Perceptions Matter: Do Divergent Views of Management and Colleagues on Social Climate Drive Employee Engagement Through Organizational Identification and Growth Satisfaction? - Galy Binyamin (SAGE Open, 2024)
A growing body of research has explored the conditions that motivate employees to engage at work. While employees’ attitudes and behaviors are socially influenced by their significant others’ perceptions, the divergent perceptions of organizational climate are underexplored. This study examines the socio-psychological mechanisms by which employees’ and managers’ perceptions of social climate enhance employee engagement at work. Based on the postulate that “ psychological state engagement” are the primary catalyst for “ behavioral engagement,” this study presents a serial mediation model that examines the role of divergent perceptions of social climate (as characterized by cooperation, shared codes and language, benevolence, and integrity) in fostering individual engagement through the mechanisms of organizational identification and growth satisfaction. Data were collected from both managers and employees, using a time-lagged design at two-time points. The findings revealed that managers’ collective perceptions of social climate were associated with organizational identification and growth satisfaction, which in turn fostered employee engagement at work. Contrary to expectations, there was no statistically significant relationship between employees’ collective perceptions of social climate and their engagement. However, individuals who had more favorable perceptions of the social climate (compare to colleagues’ collective perception) reported higher levels of organizational identification. These results point to ways in which social climate can impact employee engagement, and underscore the importance of taking divergent perceptions of organizations into account. They advance theories on the inherent tension between individuals’ desire for inclusion and the need to maintain a sense of individuality and distinctiveness.